The collection of NFATc1-dependent transcripts in the osteoclast includes numerous genes non-essential to physiologic bone resorption - Charles, Julia F.; Coury, Fabienne; Sulyanto, Rosalyn; Sitara, Despina; Wu, Jing; Brady, Nicholas; Tsang, Kelly; Sigrist, Kirsten; Tollefsen, Douglas M.; He, Li; Storm, Daniel; Aliprantis, Antonios O. (Bone (New York, N.Y.), 2012)
Osteoclasts are specialized secretory cells of the myeloid lineage important for normal skeletal homeostasis as well as pathologic conditions of bone including osteoporosis, inflammatory arthritis and cancer metastasis. Differentiation of these multinucleated giant cells from precursors is controlled by the cytokine RANKL, which through its receptor RANK initiates a signaling cascade culminating in the activation of transcriptional regulators which induce the expression of the bone degradation machinery. The transcription factor nuclear factor of activated T-cells c1 (NFATc1) is the master regulator of this process and in its absence osteoclast differentiation is aborted both in vitro and in vivo. Differential mRNA expression analysis by microarray is used to identify genes of potential physiologic relevance across nearly all biologic systems. We compared the gene expression profile of murine wild-type and NFATc1-deficient osteoclast precursors stimulated with RANKL and identified that the majority of the known genes important for osteoclastic bone resorption require NFATc1 for induction. Here, five novel RANKL-induced, NFATc1-dependent transcripts in the osteoclast are described: Nhedc2, Rhoc, Serpind1, Adcy3 and Rab38. Despite reasonable hypotheses for the importance of these molecules in the bone resorption pathway and their dramatic induction during differentiation, the analysis of mice with mutations in these genes failed to reveal a function in osteoclast biology. Compared to littermate controls, none of these mutants demonstrated a skeletal phenotype in vivo or alterations in osteoclast differentiation or function in vitro. These data highlight the need for rigorous validation studies to complement expression profiling results before functional importance can be assigned to highly regulated genes in any biologic process. ► Microarray profiling was used to identify NFATc1 dependent transcripts in the osteoclast. ► These NFATc1 dependent transcripts encompass 80 genes, including 4 known osteoclast regulators. ► Five candidate regulators were selected for study: Nhedc2, Serpind1, Adcy3, Rhoc and Rab38. ► Mutant mice in each of these genes exhibited normal bone mass and osteoclast function.